PENGARUH PEMBERIAN PHOTOSYNTHETIC BACTERIA TERHADAP PERTUMBUHAN DAN HASIL CAISIM DI TANAH GAMBUT PEDALAMAN: EFFECT OF PHOTOSYNTHETIC BACTERIA ON GROWTH AND YIELD OF CAISIM IN INLAND PEAT SOIL - Tarigan, Nirloveti Br; Widiastuti, Lusia; Pandriyani, Pandriyani; Redin, Herry; Widiyawati, Wahyu (AgriPeat, 2025)
The purpose of this study was to determine the best dose of PSB application on the growth of caisim plants in inland peat soil, and to determine the yield of caisim plants after PSB application in inland peat soil. This research was conducted in the field of Department of Agricultural Cultivation, University of Palangka Raya. This research was conducted from February 28, 2025 to April 28, 2025. This study used a single-factor Completely Randomized Design (CRD), namely the application of PSB (ml L-1) consisting of 5 treatment levels, namely: control, 25, 50, 75, and 100. Each treatment was repeated 4 times, resulting in 20 experimental units. The results showed that the application of PSB had a significant effect on the observation variables of plant height at all ages, number of leaves at 21 HST and 28 HST, plant fresh weight and plant dry weight. PSB application did not significantly affect the observation variables of the number of leaves at the age of 14 HST, leaf area and plant root weight. PSB application with a concentration of 100 ml L-1 =A4 gives the best results in all observations.